Anthracnose and leaf spot diseases of Aloe vera L. from Bangladesh - Shutrodhar, Anita Rani; Shamsi, Shamim (Dhaka University Journal of Biological Sciences, 2013)
Characteristic symptoms of anthracnose and leaf spot were recorded from diseased leaf samples of Aloe vera L. A total of 8 fungal species, namely Alternaria pluriseptata (Karst. & Har.) Jorstad, Aspergillus flavus Link, Aspergillus niger Van Tieghem, Cladosporium oxysporum Berk. & Curt., Colletotrichum gloeosporioides (Penz.) Sacc., Nigrospora oryzae (Berk. & Br.) Petch, Penicillium sp. and Pestalotiopsis guepinii (Desm.) Stay. were found to be associated with healthy and diseased leaf samples. In addition to above 8 fungi, Curvularia brachyospora Boedijn, Epicoccum purpurascens Ehrenb. ex Schlecht and Sclerotium sp. were also associated with diseased leaf samples of the plant. The prevalence of the fungi ranged 1.43 - 13.35% on healthy leaves and 1.43 - 62.16% on infected leaves. The frequency of C. gloeosporioides was the maximum and that of Aspergillus and Penicillium was the lowest. Pathogenicity test revealed that C. gloeosporioides causes anthracnose and E. purpurascens and P. guepinii cause leaf spots of A. vera. Dhaka Univ. J. Biol. Sci. 22(2): 103-108, 2013 (July)